Stanowisko Polski wobec agresji Rosji na Ukrainę. Perspektywy akcesji Ukrainy do Unii Europejskiej i NATO - Fiszer, Józef M. (Studia Polityczne, 2024)
The article aims to analyze Poland’s position on Russia’s aggression against Ukraine on February 24, 2022 and tries to show the prospects of its membership in the European Union and NATO. The undeclared war between Russia and Ukraine has been going on de facto since 2014, since the illegal annexation of the Crimean Peninsula to the Russian Federation. Since then and Russia’s aggression against Georgia in 2008, the West, led by the US, has been promising Ukraine membership in NATO and the European Union but for now, formal negotiations have not even begun. In this article, the author tries to answer why this is happening and, at the same time analyzes Poland’s position on Russia’s aggression against Ukraine in 2022 and its Euro-Atlantic aspirations. The main thesis is the statement that Ukraine’s accession to NATO and the European Union is in the Polish national interest and will not be without significance for Poland’s security.